Back to the future : the complete trilogy [videorecording (DVD)]. - Zemeckis, Robert, 1952-; Gale, Bob, 1951-; Fox, Michael J., 1961-; Lloyd, Christopher, 1938-; Thompson, Lea, 1961-; Glover, Crispin; Wilson, Thomas F., 1959-; Tolkan, James, 1931-; Weissman, Jeffrey, 1958-; Siemaszko, Casey, 1961-; Zane, Billy; Cohen, J. J. (Jeffrey Jay), 1965-; et al. (Universal Studios Home Entertainment, 2020)
Back to the future: Small-town California teen Marty McFly is thrown back into the '50s when an experiment by his eccentric scientist friend Doc Brown goes awry. Traveling through time in a modified DeLorean car, Marty encounters young versions of his parents and must make sure that they fall in love or he'll cease to exist. Even more dauntingly, Marty has to return to his own time and save the life of Doc Brown.